Investigation on Composites Reinforced with Multi-Layer Carbon Fiber and Silicone Rubber Against Impact test and Shoot Strength. - Sakuri, Sakuri; Sugiarto, Tris; Sugiantoro, Bambang; Sutarno, Sutarno; Faqih, S; Pratiwi, Yuliyanti Dian; Sutisna, Utis; Praharto, YB (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The aim of this study is to examine the durability of composite materials reinforced with carbon fiber and the effects of silicone rubber on the composites’ tensile strength, bending, firing, impact, and density. The silicon fiber was mixed with resin using a magnetic stirrer at 250 rpm, with a temperature of 40o C for 30 minutes. Furthermore, the composite production process was carried out using a vacuum infusion method with carbon fiber sheet variations of 6, 8, and 10. Tensile strength shows a proportional increase with the number of carbon fiber layers. Flexural strength indicates the opposite. The impact test was conducted in accordance with the ASTM E 23 standard, the firing test was performed using a 9x19 mm caliber bullet with a distance of 10 m, and the density was found by employing ASTM 792-13. The greatest density was 1,274 grams/cm3, and it was gotten from the sample with 10 fiber layers. Following this, the results of the impact test (Izod) showed that the specimen with 6 layers of carbon fiber had the highest impact strength of 0.040 Joule/mm. While the shoot test results indicated that the composite with 6 layers of carbon had smaller shot holes. There was no significant absorption in the water absorption test.